Determination of Biomass Yield, Forage Quality and Mineral Content of Pearl Millet Varieties (Pennisetum glaucum (L.) R. Br.) Under Semi-Arid Conditions - Sayğıdar, Niyazi; Yucel, Celal; Taş, Timuçin (My University, 2024)
With the continuous growth of the world population and Türkiye, researchers are investigating quality forage alternatives to satisfy the expanding demands of livestock. The promotion of pearl millet (Pennisetum glaucum (L.) R. Br.) as a summer crop and a potential green forage source during the summer season is significant. This study was conducted to determine the biomass yield and forage quality values of some pearl millet varieties under the second crop conditions in Akcakale/Sanlıurfa. The stalks of plants were harvested in the soft dough stage of the seeds in the panicle. In addition to biomass yield and components, quality traits in dry biomass were also determined this study. Significant statistical differences were found among all examined varieties in the yield components of biomass. Plant height (PH, cm), Number of leaves per main stem (MSL, number), Number of tillers per plant (PTN Number), Biomass yield (BY, kg da-1) and Dry biomass yield (DBY, kg da-1) varied between 198-341 cm, 11.1-15.7 number, 7.45- 12.30 number, 5938-12571 kg da-1 and 1847-3666 kg da-1 respectively. Moreover, significant and positive correlations were identified between DBY and BY, PH, MSL. As a result of the study, while, the White variety showed better performance in components of yield, the Ashana variety performed better in terms of forage quality. Moreover, Yellow and Tifleaf III varieties have CP values above 10%. Based on high biomass yield and moderate forage quality of the pearl millet varieties in the study, Pearly millet could play an important role in closing the forage deficit of ruminant animals, especially in arid and semi-arid ecologies around the world and Türkiye.
Keywords: Quality; Semi-arid; Forage yield; Variety; Pearl millet (Pennisetum glaucum (L.) R. Br.)